Pharmacognostic Evaluation Of Phyllanthus Emblica Linn (Euphorbiaceae) - D. A. DHALE (International Journal of Pharma and Bio Sciences, 2012)
The present communication deals with the pharmacognostic investigations on Phyllanthus emblica Linn(Euphorbiaceae). It is a tree of small or moderate size with a greenish-grey bark and greenish-yellow flowers, formed in auxiliary clusters. The feathery leaves are linear-oblong, with a rounded base and obtuse or acute apex. The tender fruits are green, fleshy, globose and shining, and change to light yellow or brick-red when mature. It grows in tropical and subtropical parts of China, India, Indonesia, and on the Malay Peninsula. The fruits are known as Amalakam and Sriphalam in Sanskrit, Emblic myrobalam and Indian gooseberry in English. The paper aims to identify and differentiate various anatomical features such as root and stem vessels, anatomy of node, leaf anatomy, petiole anatomy and leaf epidermis includes quantitative microscopy viz., like stomatal frequency (SF), stomatal index (SI), vein islet number (VIN) and vein termination (VTN), for evaluating the selected species. In addition, physicochemical analysis such as moisture contents, different ash values, different extractive values and effect of different chemicals on powder and extracts as well as quantitative estimation of various phytochemicals have been studied.